Prediction of signal attenuation due to duststorms using mie scattering - Islam, Md. Rafiqul; Elabdin, Zain; Elshaikh, Omer; Khalifa, Othman Omran; Alam, A. H. M. Zahirul; Khan, Sheroz; Naji, Ahmed Wathik (IIUM Press, 2010)
The present trend in radio design calls for the use of frequencies above 40 GHz for short links carrying wide-band digital communication signals. In order to utilize the new frequency band efficiently, signal attenuation studies due to duststorms is needed urgently for desert areas. This paper presents a mathematical model which has been developed to predict the signal attenuation due to duststorm. The proposed model enables the convenient calculation of the signal path attenuation based on Mie solution of Maxwell's equations for the scattering of electromagnetic wave by dust particles. The predicted values from the proposed mathematical model are compared with the measured values observed in Saudi Arabia and Sudan and show relatively close agreement.